Inflationary Expectations and Price Setting Behavior - Fair, Ray C. (The Review of Economics and Statistics, 1993)
This paper tests for the existence of expectational effects in very disaggregate price equations. Price equations are estimated using monthly data for each of 40 products. The dynamic specification of the equations is also tested, including whether the equations should be specified in level